ChemInform Abstract: One‐Step Protection‐Free Synthesis of 3‐Aryl‐5‐hydroxyalkyl‐1, 2, 4‐oxadiazoles as Building Blocks. Issue 1 (7th January 2014) - Neves Filho, Ricardo A. W.; da Silva‐Alves, Diana C. B.; dos Anjos, Janaina V.; Srivastava, Rajendra M.
Abstract A simple and straightforward route for the synthesis of the title substituted oxadiazoles via reaction of arylamidoximes (I) with glycolate derivatives is developed.